experimental interpretive processes from three-dimensional artistic production (Revista Electrónica REDINE, 2018)
This article is a reserch about the work processes within the Experimental Sculpture Workshop (Humanities and Arts Faculty DEHA-UCLA), where experience systematization was employed from activities made within it, the production of experimental charts was used as a tool for comprehending the materials transformation both experimentally and interpretively, using mixed method to achieve a deeper study of artistic production. An initial insert is made to distinct arts research and arts for arts’ sake, to explain the basic concept of research-creation by contextualizing the systematization made from the activities done in the workshop, presenting inputs which explain the mixed character of the lived experience, contributing in the comprehension of three-dimensional plastic arts creative act. The  methodology applied is shown in the workshop exercises starting from the Interpretive Paradigm, being a descriptive field  research, which brings two procedures: experimental and hermeneutic theory, it establishes a research which is thought to be merely plastic, it also brings out scientific research within the manipulation of causal, external or resulting premises expressed in summary charts the developed process.
Keywords: research creation; experimental sculpture; mixed method